Implications for Gondwana of new Ordovician paleomagnetic data from igneous rocks in southern Victoria Land, East Antarctica (Dataset) ... - Grunow, Anne M. (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Implications for Gondwana of new Ordovician paleomagnetic data from igneous rocks in southern Victoria Land, East Antarctica ...